Enhanced light–matter interaction of aligned armchair graphene nanoribbons using arrays of plasmonic nanoantennas. (16th July 2018) - Pfeiffer, Markus; Senkovskiy, Boris V; Haberer, Danny; Fischer, Felix R; Yang, Fan; Meerholz, Klaus; Ando, Yoichi; Grüneis, Alexander; Lindfors, Klas
Abstract: We couple photoluminescent semiconducting 7-atom wide armchair edge graphene nanoribbons to plasmonic nanoantenna arrays and demonstrate an enhancement of the photoluminescence and Raman scattering intensity of the nanoribbons by more than an order of magnitude averaged over large areas, and by three orders of magnitude in the hot spots of plasmonic antennas. The increase in signal allows us to study Raman spectra with high signal-to-noise ratio. Using plasmonic enhancement we are able to detect the off-resonant Raman scattering from the modified radial breathing-like mode (RBLM) due to physisorbed molecules, the 3rd order RBLM, and C-H vibrations. We find excellent agreement between experimental data and simulations describing the spectral dependence of the enhancement and modifications of the polarization anisotropy. The strong field gradients in the optical near-field further allow us to probe the subwavelength coherence properties of the phonon modes in the nanoribbons. We theoretically model this considering a finite phonon correlation length along the GNR direction. Our results allow estimating the correlation length in graphene nanoribbons.